THE CONCEPT OF DEVELOPING THE DEPARTMENT FOR PHYSICAL TRAINING IN NEW SOCIAL AND ECONOMIC CIRCUMSTANCES - L. В. Andryushchenko; T. N. Shutova (Вестник Российского экономического университета имени Г. В. Плеханова)
The research deals with the development of teaching, research, organizational and administrative, commercial activity of departments for physical training in today’s social and economic circumstances. The authors of the article put forward the concept aiming at broadening further education services, at research in the field of students’ and employees’ health control, at using technological achievements for managing the teaching process in physical culture, at differentiation of the teaching process for students freed from classes and students of special medical groups. Innovation of technological support of the teaching process in physical culture includes setting of the local informationeducational media, i.e. network e-journal. The directions of the Concept have image nature, which meet current social and economic conditions and strategy of higher education development. As a result of the Concept introduction the teaching process and further education activity were diversified and systematized. Apart from that in 2017 the volume of publications of the faculty increased by 90%.